Murine colon organoids as a novel model to study Trypanosoma cruzi infection and interactions with the intestinal epithelium - Daghero, Hellen; Pagotto, Romina; Quiroga, Cristina; Medeiros, Andrea; Comini, Marcelo A.; Bollati-Fogolín, Mariela (Frontiers in Cellular and Infection Microbiology, 2023)
Chagas disease (CD) is a life-threatening illness caused by the parasite Trypanosoma cruzi (T. cruzi). With around seven million people infected worldwide and over 50,000 deaths per year, CD is a major public health issue in Latin America. The main route of transmission to humans is through a triatomine bug (vector-borne), but congenital and oral transmission have also been reported. The acute phase of CD presents mild symptoms but may develop into a long-lasting chronic illness, characterized by severely impaired cardiac, digestive, and neurological functions. The intestinal tissue appears to have a key role during oral transmission and chronic infection of CD. In this immune-privileged reservoir, dormant/quiescent parasites have been suggested to contribute to disease persistence, infection relapse, and treatment failure. However, the interaction between the intestinal epithelium and T. cruzi has not been examined in depth, in part, due to the lack of in vitro models that approximate to the biological and structural complexity of this tissue. Therefore, to understand the role played by the intestinal tissue during transmission and chronic infection, physiological models resembling the organ complexity are needed. Here we addressed this issue by establishing and characterizing adult stem cell-derived colonoid infection models that are clinically relevant for CD. 3D and 2D systems of murine intestinal organoids infected with T. cruzi Dm28c (a highly virulent strain associated with oral outbreaks) were analyzed at different time points by confocal microscopy. T. cruzi was able to invade and replicate in intestinal epithelial primary cells grown as intact organoids (3D) and monolayers (2D). The permissiveness to pathogen infection differed markedly between organoids and cell lines (primate and intestinal human cell lines). So far, this represents the first evidence of the potential that these cellular systems offer for the study of host-pathogen interactions and the discovery of effective anti-chagasic drugs.